RNA-Induced Conformational Switching and Clustering of G3BP Drive Stress Granule Assembly by Condensation - Guillen-Boixet, Jordina; Kopach, Andrii; Holehouse, Alex S.; Wittmann, Sina; Jahnel, Marcus; Schluessler, Raimund; Kim, Kyoohyun; Trussina, Irmela R. E. A.; Wang, Jie; Mateju, Daniel; Poser, Ina; Maharana, Shovamayee; et al. (Cell, 2020)
Reconstitution of stress granule assembly reveals an autoinhibitory conformation of G3BP that is alleviated by RNA binding, demonstrating how this central node of the stress granule network phase-separates in response to rising cellular RNA concentrations.
CRIS-Team Scopus Importer:2022-08-05
Keywords: G3BP; liquid-to-solid transition; Neurodegenerative disease; phase separation; RNP granules; stress granules; stress response